The Error in the Groundwork: Kant's Revision of the Imperatives and Prudence as Technical Ability - Bacin, Stefano (Studia Kantiana, 2023)
The paper examines Kant's self-criticism to the account of hypothetical imperatives given in the Groundwork for the Metaphysics of Morals. Following his corrections in the introductions to the third Critique, the paper traces the consequences of that change in his later writings, specifically with regard to the status of prudence. I argue that the revision of the account of hypothetical imperatives leads to differentiate, and ultimately separate, two functions in prudence: the setting of ends through maxims, and the pragmatic rules establishing means to reach those ends. Accordingly, I furthermore argue, there is ultimately no genuine structural distinction between the rules of prudence and skill. The only difference lies in the domain in which prudence unfolds, that is, the field of human relations, and in the relevant cognitions.